Catechin and quercetin attenuate adipose inflammation in fructose‐fed rats and 3T3‐L1 adipocytes - Vazquez Prieto, Marcela Alejandra (2015)
Scope This study evaluated the capacity of dietary catechin (C), quercetin (Q), and the combination of both (CQ), to attenuate adipose inflammation triggered by high fructose (HFr) consumption in rats and by tumor necrosis factor alpha (TNF‐α) in 3T3‐L1 adipocytes. Methods and results In rats, HFr consumption for 6 wk caused dyslipidemia, insulin resistance, reduced plasma adiponectin, adiposity, and adipose tissue inflammation. Dietary supplementation with 20 mg/kg/day of C, Q, and CQ improved all these parameters. In 3T3‐L1 adipocytes, C and Q attenuated TNF‐α‐induced elevated protein carbonyls, increased proinflammatory cytokine expression (MCP‐1, resistin), and decreased adiponectin. The protective effects of C and Q on adipose inflammation are in part associated with their capacity to (i) decrease the activation of the mitogen‐activated kinases (MAPKs) JNK and p38; and (ii) prevent the downregulation of PPAR‐γ. In summary, C and Q, and to a larger extent the combination of both, attenuated adipose proinflammatory signaling cascades and regulated the balance of molecules that improve (adiponectin) or impair (TNF‐α, MCP‐1, resistin) insulin sensitivity. Conclusion Together, these findings suggest that dietary Q and C may have potential benefits in mitigating MetS‐associated adipose inflammation, oxidative stress, and insulin resistance.